Chemoreaction Drying of Saccharomyces cerevisiae Culture with CaO and the Influence of Moisture Sorption Upon Stress and Death of the Dried Culture - Novelina .; Soewarno T Soekarto; Betty Sri Laksmi Jenie; Susono Saono; Maggy T Suhartono (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2005)
The aim of the research was to study chemoreaction drying of Saccharomyces cerevisiae culture and to a analyze the influence of moisture sorption on pattern of viability, stress and mortality of the dried starter culture. The cell culture of S. cerevisiae was produced in glucose media with aerobic process in a fermentor at 30C. The cell obtained was dried in a using chemoreaction process. Drying was conducted by coating with various thickness of coating and various ratio of CaO and calcium oxide ratio used in drying. Dry culture of S. cerevisiae and protective agent of CMC and jelly were added to the dry culture. The mixtrure then was stored at in decicators at R H 11 up to 97% until water equilibrium was achieved. Later the patterns of stress from each sample of dry culture at various conditions of moisture was analyzed. The result of the research showed that the best drying method was using coat thickness of 1.3 mm and calcium oxide 10 times the weight of dried sample. The condition of dry culture at low minimal water from 5 % were mostly in dormant state, the highest viability was at the rate of moisture of 5 % - 8 %, but a lot portion of the cells were inactive, and at the moisture higher than 8%, dead cells were observed. Addition 2% jelly of 2% CMC did not protect cells from stress. Key words: Saccharomyces cerevisiae, chemoreaction drying, moisture sorption, dry stresses